2018
DOI: 10.1016/j.aca.2018.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of oligo(acrylic acid)s and their block co-oligomers

Abstract: Oligo(acrylic acid), oligoAA are important species currently used industrially in the stabilization of paints and also for the production of self-assembled polymer structures which have been shown to have useful applications in analytical separation methods and potentially in drug delivery systems. To properly tailor the synthesis of oligoAA, and its block co-oligomers synthesized by Reversible-Addition Fragmentation chain Transfer (RAFT) polymerization to applications, detailed knowledge about the chemical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…11) This core-shell type NPs were fabricated from inexpensive, commercially available and easy to handle materials, and therefore it can be expected to use as a good candidate for the alternative of Nafion®. [12][13][14] In this system, the interface between the silanol group (-SiOH) from the surface of silica NPs and the carboxylic group (-COOH) of coated PAA form the proton conductive channels which are significantly critical for proton conductivity of this PEM system. 6,11,15) The coated PS provides several functions to this PEM, one is suppressing the swelling of the PAA under the PEFC operation with high humidity, indicating that coated PS contributes to long-term stable PFECs operation with maintaining PFEC performance under high humidity operation.…”
Section: Introductionmentioning
confidence: 99%
“…11) This core-shell type NPs were fabricated from inexpensive, commercially available and easy to handle materials, and therefore it can be expected to use as a good candidate for the alternative of Nafion®. [12][13][14] In this system, the interface between the silanol group (-SiOH) from the surface of silica NPs and the carboxylic group (-COOH) of coated PAA form the proton conductive channels which are significantly critical for proton conductivity of this PEM system. 6,11,15) The coated PS provides several functions to this PEM, one is suppressing the swelling of the PAA under the PEFC operation with high humidity, indicating that coated PS contributes to long-term stable PFECs operation with maintaining PFEC performance under high humidity operation.…”
Section: Introductionmentioning
confidence: 99%
“…This method was recently applied by Sutton et al for the separation of oligo(acrylic acid)s through free solution capillary electrophoresis. 36 We observed that oligomers containing NAP could be visualized after running polyacrylamide gel electrophoresis (PAGE) and staining with GelRed®, a molecule used to stain DNA (Figure 2b). The cationic and aromatic GelRed® molecules most likely interact electrostatically with the anionic oligo(phosphodiester)s, and with NAP units via π-π stacking.…”
Section: Purification Of Sequence-defined Block Co-oligo(phosphodiester)smentioning
confidence: 99%
“…The instrumental parameters for one-dimensional 15 and twodimensional 63 NMR were described in accompanying publications. One-dimensional NMR conditions like the concentration, number of scans, repetition delay, solvent were described in earlier work 15 but also summarized with the information for additional samples in the Supporting Information (Table S2).…”
Section: Nmr Spectroscopymentioning
confidence: 99%